Fluorogenic Protein‐Based Strategies for Detection, Actuation, and Sensing. (28th August 2018) - Gautier, Arnaud; Tebo, Alison G.
Abstract : Fluorescence imaging has become an indispensable tool in cell and molecular biology. GFP‐like fluorescent proteins have revolutionized fluorescence microscopy, giving experimenters exquisite control over the localization and specificity of tagged constructs. However, these systems present certain drawbacks and as such, alternative systems based on a fluorogenic interaction between a chromophore and a protein have been developed. While these systems are initially designed as fluorescent labels, they also present new opportunities for the development of novel labeling and detection strategies. This review focuses on new labeling protocols, actuation methods, and biosensors based on fluorogenic protein systems. Abstract : This review presents recently developed fluorogenic protein‐based systems made of a protein tag incorporating an external chromophore. Beyond addressing some limitations of classical fluorescent proteins, these unique systems present characteristics than can be used to creatively push the limits of biological imaging, in particular for the development of new labeling protocols, actuation methods and biosensors.